1998
DOI: 10.1002/(sici)1097-4636(199810)42:1<30::aid-jbm5>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of aortic wall calcification in bioprosthetic heart valves by ethanol pretreatment: Biochemical and biophysical mechanisms

Abstract: The effectiveness of ethanol pretreatment on preventing calcification of glutaraldehyde-fixed porcine aortic bioprosthetic heart valve (BPHV) cusps was previously demonstrated, and the mechanism of action of ethanol was attributed in part to both lipid removal and a specific collagen conformational change. In the present work, the effect of ethanol pretreatment on BPHV aortic wall calcification was investigated using both rat subdermal and sheep circulatory implants. Ethanol pretreatment significantly inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 30 publications
3
50
0
2
Order By: Relevance
“…A second approach consisted of treating isolated calcospherulites on electron microscopy grids with ice-cold 70% ethanol in order to selectively remove phospholipids ( Fig. 4B; ethanoltreated TEM) [27,28], and submitting them to EDS. Such analysis revealed the presence of ethanol-extractable phosphorus from isolated calcospherulites ( Fig.…”
Section: Isolated Calcospherulites Likely Contain Phospholipidsmentioning
confidence: 87%
See 1 more Smart Citation
“…A second approach consisted of treating isolated calcospherulites on electron microscopy grids with ice-cold 70% ethanol in order to selectively remove phospholipids ( Fig. 4B; ethanoltreated TEM) [27,28], and submitting them to EDS. Such analysis revealed the presence of ethanol-extractable phosphorus from isolated calcospherulites ( Fig.…”
Section: Isolated Calcospherulites Likely Contain Phospholipidsmentioning
confidence: 87%
“…Our studies revealed the presence of ethanol-extractable phosphorus in isolated calcospherulites, and future studies will identify and quantify the nature of this extractable phosphorus. Since nucleic acids, proteins, and complex carbohydrates are insoluble in cold ethanol solutions, then the most likely molecular candidate to explain this ethanolextractable phosphorus would be phospholipids [27,28]. If true, then an apparent association of phospholipids with calcospherulites would be consistent with the concept that some type of matrix vesicle aggregation phenomenon could permit the transition of some of their contents to become calcospherulites [35].…”
Section: Discussionmentioning
confidence: 99%
“…Gramicidin D, BA, and radioactive [carboxy- 14 C] BA (specific activity, 250 mCi/mmol) were purchased from Sigma (St Louis, MO). HEPES-buffered (25 mM ) Hank's balanced salt solution (HHBSS) was used as a receptor solution.…”
Section: Methodsmentioning
confidence: 99%
“…Following 12-hour permeation studies using radioactive [carboxy- 14 C] BA (100 µ g), skin samples were carefully rinsed 5 times with 1 ml of water. The skin was placed epidermis side up on a board lined with a parafilm.…”
Section: Evaluation Of Drug Distribution In the Membranementioning
confidence: 99%
“…O etanol apresentou efeito anticalcificante no pericárdio bovino de implantes subcutâneos em ratos e de próteses mitrais em ovelhas (18)(19)(20) . Vários estudos têm demonstrado a eficácia do etanol como inibidor da calcificação de biopróteses porcinas, sendo seu principal efeito a extração lipídica (1,18,20,21) .…”
Section: Introductionunclassified